Training effectiveness: An exploratory study of Pasukan Latihan Pegawai Simpanan (Palapes) Universiti Utara Malaysia / Mohammad Bastyian Mahmud, Khalilah Ibrahim And Noor Azzura Mohamed - Mahmud, Mohammad Bastyian; Ibrahim, Khalilah; Mohamed, Noor Azzura (2012)
The aim of this study is to examine the effectiveness of training in Pasukan Latihan Pegawai Simpanan (PALAPES) by exploring the trainee's effects, trainer's encouragement and the effect of goal orientation. The government especially Ministry of Defence have spents RM8.2 million a year to manage the training and exercises as well as clothing allowances whereby excluding the trainer salary and building infrastructure (Ministry of Defence, 2004). Even though there could be fewer research on training effectiveness of PALAPES, this exploratory study might be the stepping stone to examine the effectiveness of PALAPES's training. The findings of this study suggest that to improve the training, PALAPES should determine the trainee's motivation and voluntarily before they join PALAPES; the trainer give encouragement to make sure the cadets could apply what they have learned in the training sessions; and PALAPES could set their goal orientation why they should join and achieved in the end of their training. Therefore, by improving this training through these variables, the training effectiveness of PALAPES can be achieved.